Extraction of Ibuprofen from Bougainvillea Campanulata and Its Method Development and Validation - Velraj, Malarkodi; Shah, Vishal; Khan, Niyamat; Arshad, Mohd Sajid; Raman, S. G.; B Jadhav, Aniruddha; elakkiya, S. Manodhini; Preethi N; Jahnavi, Patibandla (Journal of Neonatal Surgery, 2025)
Background: The extraction of ibuprofen from Bougainvillea campanulata and the creation and approval of a reliable technique for its separation and measurement are the main objectives of this investigation. This study will contribute to the growing body of knowledge regarding the use of plant-based sources for therapeutic compounds and set the stage for future research into Bougainvillea campanulata as a potential natural source of ibuprofen. Aim: This work aimed to develop and evaluate a UV-visible spectrophotometric approach utilizing FTIR to accurately, precisely, and straightforwardly quantify the concentration of ibuprofen in an extract. Material and Methods: In the experiment, methanol served as the solvent. It was determined that the drug's absorption maximum (λmax) was 265 nm. Beer's law was followed between 100 μg/ml and 500 μg/ml. Results: A correlation coefficient of 1 and the equation y = 0.000023x signify that the approach exhibits linearity with respect to the given concentrations. The extract contained 7 µg/ml of ibuprofen. Ibuprofen extracted from Bougainvillea Campanulata flowers had recovery percentages between 85.9% and 87.6%. The intraday precision was 42.95%, while the interday precision was 51.35%, both quantified as relative standard deviation (RSD%). The quantification limit was 2.70 μg/mL, while the detection limit was 0.90 μg/mL. The method's robustness percentage ranged from 37.43% to 45.86% regarding relative standard deviations. Conclusion: The proposed methodology was accurate, exact, and economical. This technique may effectively ascertain the methanol concentration in an extract obtained from bougainvillea flowers.